An Application of ASP in Nuclear Engineering: Explaining the Three Mile Island Nuclear Accident Scenario. Issue 6 (November 2020) - HANNA, BOTROS N.; TRIEU, LY LY T; SON, TRAN C.; DINH, NAM T.
Abstract: The paper describes an ongoing effort in developing a declarative system for supporting operators in the Nuclear Power Plant (NPP) control room. The focus is on two modules: diagnosis and explanation of events that happened in NPPs. We describe an Answer Set Programming (ASP) representation of an NPP, which consists of declarations of state variables, components, their connections, and rules encoding the plant behavior. We then show how the ASP program can be used to explain the series of events that occurred in the Three Mile Island, Unit 2 (TMI-2) NPP accident, the most severe accident in the USA nuclear power plant operating history. We also describe an explanation module aimed at addressing answers to questions such as "why an event occurs?" or "what should be done?" given the collected data.